Penerapan EPA SWMM 5.2 pada Sistem Drainase untuk Mereduksi Banjir di Perumahan Sukolilo - Setyowati, Rr Diah Nugraheni Setyowati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The application of EPA SWMM 5.2 is needed to reduce flooding in Sukolilo Housing, because the housing was built by filling land so it changes the land use from a pond area to a runoff area, causing flooding. The method used in this study is a quantitative descriptive method. This study's aim is to simulate and optimize the capacity of the Sukolilo Housing drainage network using the SWMM 5.2 software program. In this study, hydrological and hydraulic simulations were carried out using SWMM 5.2 software which can represent flow and inundation spatially and temporally. Further analysis was carried out using a hydrological and hydraulic approach to calculate the planned rainfall and runoff discharge resulting from each extreme rain event. The simulation was carried out on the existing drainage network model by entering actual parameters including base elevation, channel cross-section dimensions, channel shape, and network layout with a site plan map of the area. After the latest simulation was carried out, the results were obtained, namely enlarging the secondary channel to 0.80 m × 0.80 m and reducing the tertiary channel to 0.50 m × 0.35 m, the flow capacity increased significantly without sacrificing hydraulic performance and saving material usage.